2021
DOI: 10.1021/acschemneuro.1c00351
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functionalized Amino Acids as Inhibitors of GABA Transporters with Analgesic Activity

Abstract: Neuropathic pain resistance to pharmacotherapy has encouraged researchers to develop effective therapies for its treatment. γ-Aminobutyric acid (GABA) transporters 1 and 4 (mGAT1 and mGAT4) have been increasingly recognized as promising drug targets for neuropathic pain (NP) associated with imbalances in inhibitory neurotransmission. In this context, we designed and synthesized new functionalized amino acids as inhibitors of GABA uptake and assessed their activities toward all four mouse GAT subtypes (mGAT1–4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…MD simulations were performed in NAMD 2.13 using the CHARMM36m force field. Complexes were positioned in the membrane using the OPM server, and input files for MD simulations were prepared with the CHARMM-GUI online server following the same settings mentioned in our previous papers [ 53 , 61 , 62 ]. The system was equilibrated via a six-step protocol, and MD simulations were run at 303.15 K with a time step of 2 fs and a total duration of 50 ns.…”
Section: Methodsmentioning
confidence: 99%
“…MD simulations were performed in NAMD 2.13 using the CHARMM36m force field. Complexes were positioned in the membrane using the OPM server, and input files for MD simulations were prepared with the CHARMM-GUI online server following the same settings mentioned in our previous papers [ 53 , 61 , 62 ]. The system was equilibrated via a six-step protocol, and MD simulations were run at 303.15 K with a time step of 2 fs and a total duration of 50 ns.…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of reduced endogenous GABAergic tone, the GABA-B receptor agonist baclofen exerts an anti-injury sensory effect and releases GABA from the cortical precursors of GABAergic interneurons transplanted into the medial ganglion bulge, ultimately reversing neuropathic abnormal pain ( 105 ). GAT proteins are highly dynamic in different cell types and are responsible for the recycling and reuptake of GABA, thereby terminating inhibitory signaling ( 106 ). Studies have reported that inhibition of GAT reuptake enhances GABAergic neurotransmission and has an inhibitory effect on the release of aspartate and glutamate in the dorsal spinal cord, thereby inhibiting the release of pro-nociceptive neurotransmitters to achieve analgesia ( 107 ).…”
Section: Future Perspectives and Challenges: Clinical Trials Related ...mentioning
confidence: 99%
“…17,88 In a recent study, novel functionalized amino acids that were designed and synthesized exhibited inhibitory effects on mGAT4 and mGAT2 transporters and showed analgesic effects in preclinical studies of 3 different NP mod-els. 88 Similarly, in another report, novel compounds inhibiting mouse GABA transporters (mGAT3/4), showed an antiallodynic effect by making GABA more available in diabetic and oxaliplatin-induced NP models. 89 Also, GAT-1 inhibitor NNC-711 and GAT-3 inhibitor SNAP-5114, by decreasing the amplitude of pain fibers mediated excitatory postsynaptic currents produced analgesia in NP mice models.…”
Section: Inhibiting Gaba Uptake and Metabolismmentioning
confidence: 99%
“…Although tiagabine is the only clinically approved GAT inhibitor for NP, several molecules and drugs are under investigation for the same [ 17 , 88 ]. In a recent study, novel functionalized amino acids that were designed and synthesized exhibited inhibitory effects on mGAT4 and mGAT2 transporters and showed analgesic effects in preclinical studies of 3 different NP models [ 88 ].…”
Section: Restoring the Inhibitory Tone Relieves Sci-cnpmentioning
confidence: 99%
See 1 more Smart Citation